The Effect of the Tourism Sector, Human Capital, And Economic Openness on Total Productivity Factors in Bali Province 1985 – 2019 - Made Suyana Utama; I Gusti Bagus Indrajaya (Jurnal Ilmiah Akuntansi, 2023)
In order to improve economic performance, increasing labor productivity is very important, because the higher the productivity of the workforce, the more its competitiveness will increase. This study aims to analyze the effect of the tourism sector, human capital, and economic openness on the total factor productivity in Bali Province. The data used is secondary data obtained from the Central Statistics Agency in the form of data on capital formation, labor, average length of schooling, and export-import in Bali Province from 1985 - 2019. The analysis technique used is multiple linear regression. The results showed that the tourism sector and the quality of human capital had a positive effect on total factor productivity in Bali Province during 1985 – 2019, while economic openness had a positive but not significant effect.